THE EFFECT FACTORS OF SUPPLY SALT IN INDONESIA - Rusdi Rusdi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
This study aims to analyze the factors that can affect the supply of Indonesian salt. The method used is quantitative method using ordinary least squares (OLS) with a multiple linear regression model. The type of data to be used in this study using secondary data time series year 2000-2014. The data are taken from a variety of sources, including the Central Bureau of Statistics, Ministry of Commerce, Ministry of Industry, Ministry of Maritime Affairs and Fisheries and other resources related to the research. The results of this study showed that the factors that significantly affect the salt deals in Indonesia is the rainfall and the PUGAR and technology not significantly. Negative coefficient of rainfall that can be explained that when there was an increase in precipitation will result in salt deals in Indonesia will go down. While the PUGAR can increase the supply of salt